The Accuracy of Transrectal Ultrasonography Diagnostic for Examination of Ovarian Structures in Cattle - Prabowo Purwono Putro (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
The study aimed to determine the accuracy of ovarian follicle and corpus luteum measurements in vivo using ultrasonography diagnostic and in vitro after slicing of the ovaries. A total of 15 cows were examined using transrectal ultrasonography just before being slaughtered. Ultrasonographic examination was performed using 7.5 MHz transrectal tranducer on ovaries, measured dominant follicle and corpus luteum diameters. Follicleappeared echogenic, black with round shape. Corpus luteum, appeared as low echogenicity structure and grayish in color.Ovaries were taken out soon after animals slaughtered, soaked in 10% buffered formalin for 12 hours,then cut in thin slices and measured follicle and corpus luteum diameters. Results of follicle and corpus luteum diameter measurements in vitro and in vivo compared using two sample or paired t-test, correlation and regression analyses. The two methods of follicle and corpus luteum measurements had linear orrelation (follicle measurement, R2 = 0.933 , r = 0.966, n = 15, P < 0.05) (corpus luteum, R2 = 0.912, r = 0.955, n = 15, P < 0.05).Measurements of dominant follicle diameter and corpus luteum size manifested the real size of the two ovarian structures. Transrectal ultrasonography diagnostic on ovaries proved to be having high accuracy and reliability for identification, measurement of ovarian structure diameters, follicle and corpus luteum in cattle.